2013
DOI: 10.1111/jsbm.12022
|View full text |Cite
|
Sign up to set email alerts
|

“How to Do Things with Words”: The Discursive Dimension of Experiential Learning in Entrepreneurial Mentoring Dyads

Abstract: (commitment, compliance, resistance) and the enterprise levels (business launching and fund-raising).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 91 publications
3
69
0
2
Order By: Relevance
“…Indeed, vicarious learning from mentors was identified as the most significant contribution to mentoring relationships, regardless of the context being studied (Barrett, 2006;Crocitto, Sullivan, and Carraher, 2005;D'Abate and Eddy, 2008;Gordon and Brobeck, 2010;Hezlett, 2005;Lankau and Scandura, 2002;St-Jean and Audet, 2012). Furthermore, mentors may use verbal persuasion strategies to help mentees explore and sometimes change their attitudes and beliefs (Marlow and McAdam, 2012;Radu Lefebvre and Redien-Collot, 2013;St-Jean and Audet, 2013). Finally, mentors may influence mentees' emotional states by reducing their levels of stress related to perceived uncertainty and future challenges (Kram and Hall, 1989;Sosik and Godshalk, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, vicarious learning from mentors was identified as the most significant contribution to mentoring relationships, regardless of the context being studied (Barrett, 2006;Crocitto, Sullivan, and Carraher, 2005;D'Abate and Eddy, 2008;Gordon and Brobeck, 2010;Hezlett, 2005;Lankau and Scandura, 2002;St-Jean and Audet, 2012). Furthermore, mentors may use verbal persuasion strategies to help mentees explore and sometimes change their attitudes and beliefs (Marlow and McAdam, 2012;Radu Lefebvre and Redien-Collot, 2013;St-Jean and Audet, 2013). Finally, mentors may influence mentees' emotional states by reducing their levels of stress related to perceived uncertainty and future challenges (Kram and Hall, 1989;Sosik and Godshalk, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Among these initiatives, the mentoring of novice entrepreneurs was emphasized as highly beneficial for enhancing entrepreneurial self-efficacy (ESE) and entrepreneurial skills (e.g. Crompton, 2012;Gravells, 2006;Radu Lefebvre and Redien-Collot, 2013;St-Jean and Audet, 2013). Extensive empirical research (Ozgen and Baron, 2007;Sullivan, 2000;Ucbasaran, Westhead, and Wright, 2008) confirmed the positive impact of mentoring relationships on both mentees' cognitions (improving opportunity identification, clarifying business vision) and emotions (reducing stress and feelings of being isolated, establishing more ambitious goals).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, they must find a mentor for their course project; an increasingly popular experiential learning method (Lefebvre and Redien-Collot 2013). One semester I experimented with randomly assigning teams and prescribing mentors to test whether students could spend less time organizing their teams and more time working on their project.…”
Section: Team Assignmentsmentioning
confidence: 99%
“…Lefebvre (2013) argues that entrepreneurship education uses mainly experiential learning to develop students" critical thinking skills, through involving them in direct experience such as launching business startups or developing business plans (Lefebvre, 2013). Experiential learning allows students to explore their knowledge and also to develop their ability to investigate the unknown, accept uncertainty and to build their self confidence (Lefebvre, 2013). According to Taras (2013), lots of studies have confirmed the effectiveness of experiential learning in business education (Taras, 2013).…”
Section: Experiential Learning For Business Educationmentioning
confidence: 99%
“…Moreover, experiential learning activities have been revealed to improve the overall students" performance and grades (Chavan, 2011). Lefebvre (2013) argues that entrepreneurship education uses mainly experiential learning to develop students" critical thinking skills, through involving them in direct experience such as launching business startups or developing business plans (Lefebvre, 2013). Experiential learning allows students to explore their knowledge and also to develop their ability to investigate the unknown, accept uncertainty and to build their self confidence (Lefebvre, 2013).…”
Section: Experiential Learning For Business Educationmentioning
confidence: 99%